(untitled) (Experimental biology, 2015)
Tan spot is one of the harmful wheat diseases in many agricultural areas of the world including Kazakhstan. Это ставит задачу создания новых сортов пшеницы на основе выявления носителей устойчивости к болезни с использованием молекулярных маркеров. Therefore it is necessary to develop of new wheat varieties on the basis of identification of carriers of resistance to disease using molecular markers. As a result of molecular screening using SSR markers Xfcp1 and Xfcp394 38 sources of effective gene tsn1, including 20 Kazakhstani varieties and advanced lines of wheat and 18 foreign entries insensitive to toxin Ptr ToxA were identified. It allowed forming identified collection of sources of tsn1 gene that could provide defense from the aggressive wheat tan spot toxin Ptr ToxA.